PERAN KEPEMIMPINAN DALAM INSEMINASI DAN PENERAPAN “INVICTUS” DALAM BUDAYA ORGANISASI GERAKAN CREDIT UNION KELING KUMANG - AS, Adil Bertus; Putra, Masri Sareb; Elvi, Fitria; Junianta, Maria (STIE Wiyatamandala, 2023)
The article discusses the crucial role of leadership in disseminating and implementing the core philosophy and values of